Fracture evolution characteristics of coal rock mass by high-voltage electric pulse fracturing in water - Xiankai BAO; Tong ZHANG; Guangqin CUI; Bin JIANG; Xiaofan ZHANG; Jianlong QIAO (Meitan kexue jishu)
High-voltage electric pulse fracturing in water is an important way to improve the efficiency of coalbed methane exploitation. To study the characteristics and laws of crack fracture in the process of high-voltage electric pulse fracturing coal rock mass in water, based on acoustic emission technology, by conducting high-pressure electric pulse stamping and fracturing tests on coal and rock masses in water, the crack fracture evolution characteristics under different discharge voltages were quantitatively analyzed using ringing and energy, and the event distribution and fractal dimension were used to analyze the crack development and propagation law, combining with the numerical simulation of PFC2D particle flow, the morphological characteristics of crack initiation and propagation were further studied from the mesoscale. The results show that: At a constant hydrostatic pressure, there are a optimal discharge times for cracking coal rock mass caused by different discharge voltages, after the optimal discharge times, the cumulative ringing count, maximum ringing count and cumulative energy of the coal rock mass specimens reach the peak, these parameters gradually decrease if the discharge time increase. With the increase of discharge voltage and times, forming a large number of microcracks and multiple X-shaped main cracks with an direction of 45°. Discharge after reaching the optimal discharge times, the number, scale and density of microcracks basically no longer increase, while the penetrating main cracks further develop and expand, and the length continues to increase. With the increase of discharge times, the fractal dimension value gradually decreases, the crack gradually adjusts from random and disordered microcracks to orderly and penetrating main cracks, and the crack complexity gradually decreases. The simulation results show that a large number of microcracks and unequal numbers of primary and secondary cracks are formed around the borehole of the coal rock mass after the discharge in the borehole water, and the length of the main crack increases significantly with the increase of discharge voltage and times. The research results can provide theoretical support for the application of high-voltage electric pulse fracturing coal rock mass reservoir technology in water.